2010
DOI: 10.2139/ssrn.1564289
|View full text |Cite
|
Sign up to set email alerts
|

Does Conflict Affect Preferences? Results from Field Experiments in Burundi

Abstract: We use experimental data from 35 randomly selected communities in Burundi to examine the impact of exposure to conflict on social-, risk-and time preferences. These types of preferences are important as they determine people's propensity to invest and their ability to overcome social dilemmas, so that changes therein foster or hinder economic growth. We find that conflict affects preferences. Individuals that have been exposed to greater levels of violence display more altruistic behavior towards their neighbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 56 publications
0
40
1
2
Order By: Relevance
“…While several studies have found that exposure to con ‡ict or to natural disasters can a¤ect risk attitudes, the direction of this e¤ect di¤ers across studies. Those studies which …nd a positive association between exposure to con ‡ict or trauma and risk-taking behavior tend to involve events much more extreme than we study here: for instance, exposure to casualties in Burundi (Voors et al, 2010) or relocation due to Hurricane Katrina (Eckel et al, 2009). In this part of Kenya, the con ‡ict was closer to a natural disaster (without as much destruction of physical capital) than to a war or a devastating hurricane, and so perhaps closer to exposure to ‡oods or hurricanes as in Cameron and Shah (2010), who …nd that exposure made people more risk averse.…”
Section: Alternative Explanationsmentioning
confidence: 70%
“…While several studies have found that exposure to con ‡ict or to natural disasters can a¤ect risk attitudes, the direction of this e¤ect di¤ers across studies. Those studies which …nd a positive association between exposure to con ‡ict or trauma and risk-taking behavior tend to involve events much more extreme than we study here: for instance, exposure to casualties in Burundi (Voors et al, 2010) or relocation due to Hurricane Katrina (Eckel et al, 2009). In this part of Kenya, the con ‡ict was closer to a natural disaster (without as much destruction of physical capital) than to a war or a devastating hurricane, and so perhaps closer to exposure to ‡oods or hurricanes as in Cameron and Shah (2010), who …nd that exposure made people more risk averse.…”
Section: Alternative Explanationsmentioning
confidence: 70%
“…Whitt and Wilson (2007) make Bosnians play the dictator game and …nd that players treat opponents from the same ethnic group with more fairness. Voors et al (2010) …nd that players who have been exposed to more violence in their past behave more altruistically to neighbors and are more risk seeking. Cassar, Grosjean and Whitt (2011) run experiments in Tajikistan and …nd that con ‡ict exposure reduces trusting and fair behavior to a larger extent in interactions with other players from the same area than with people from elsewhere.…”
Section: Related Literaturementioning
confidence: 99%
“…However, it is difficult to interpret the relevance of such results for the predictions at issue here, as minor pecuniary conflicts differ substantially from real intergroup violence. More compellingly, archival analysis indicates that the 9/11 terrorist attacks in the USA were followed by increased charitable volunteering [29], and a recent investigation in Burundi, notable for its use of experimental methods in a real-world context [30], reveals that exposure to interethnic violence correlates with increased first-order generosity in economic games [31].…”
Section: Introductionmentioning
confidence: 99%